2007
DOI: 10.1295/polymj.pj2006169
|View full text |Cite
|
Sign up to set email alerts
|

Incompletely Condensed Silsesquioxanes: Formation and Reactivity

Abstract: ABSTRACT:Hydrolysis reaction products from aryltrialkoxysilanes were studied in various solvents with alkali and alkaline earth metal hydroxides. Definite products could be isolated when sodium hydroxide was used. Reaction of trimethoxy-or triethoxyphenylsilane with equimolar amounts of sodium hydroxide to the silicon compound in refluxing water-i-propanol gave cyclic sym-cis tetraphenylsilsesquioxanetetraol tetrasodium salt as the principal product. When a little excess of sodium hydroxide than half molar amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 14 publications
2
55
0
Order By: Relevance
“…Compound 2 was recrystallized in a mixed solvent of chloroform and 2‐propanol (2:1) affording colorless crystals. A report describing the facile synthesis of 1 b , coupled with the dichlorodimethylsilane afforded T 8 D 2 ( 2 ) and set the groundwork for this procedure . However, the crystal structure of 2 was not determined with the proposed DDSQ structure at that time.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Compound 2 was recrystallized in a mixed solvent of chloroform and 2‐propanol (2:1) affording colorless crystals. A report describing the facile synthesis of 1 b , coupled with the dichlorodimethylsilane afforded T 8 D 2 ( 2 ) and set the groundwork for this procedure . However, the crystal structure of 2 was not determined with the proposed DDSQ structure at that time.…”
Section: Methodsmentioning
confidence: 93%
“…The doubly‐extended butterfly cage T 8 D 4 3 , T 8 D 6 4 , and T 8 D 8 5 , both ends of which are linked to oligosiloxane chains, were synthesized in 91 %, 86 %, 64 %, respectively by the reaction of DDSQ‐tetraol 1 a with methyl substituted oligosiloxane in the presence of triethylamine (Scheme ). Tetraol 1 a can be prepared in high yield from DDSQ‐(ONa) 4 1 b that was easily synthesized from trimethoxyphenylsilane in 2‐propanol via hydrolytic condensation using sodium hydroxide and refluxing for 4 h followed by stirring for 15 h at 20 °C according to a previously reported method . The condensation reactions between tetraol 1 a and dichlorooligosiloxanes are somewhat slow, requiring a reaction time of 14 h at room temperature and several hours at reflux.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of DD-OH was confi rmed by 29 Si-NMR and other spectroscopic analyses (Scheme 2) [10,11]. In quite recent time, Lee reported that the double-decker shaped silsesquioxane seems to be produced with the consumption of the partial cage and the cyclic siloxanes in the same condition [12].…”
Section: Introductionmentioning
confidence: 94%
“…Trisilanolphenyl POSS was synthesized from phenyltrialkoxysilane, NaOH and deioned water, and then acidified by acetic acid according to the literature method [21,22]. The solution was distilled by reduced pressure, and white crystal solid was dried under vacuum.…”
Section: Syntheses Of Trisilanolphenyl Possmentioning
confidence: 99%